Analysis of Acid-Fast Bacilli (AFB) Conversion at the 2nd and 5th Months in Tuberculosis Patients with and without Diabetes Mellitus - Chylen Setiyo Rini; Sukma Nilawati (Jurnal Laboratorium Khatulistiwa, 2026)
Tuberculosis (TB) remains a major global health problem and is often associated with comorbidities such as Diabetes Mellitus (DM). DM can impair immune response and may delay sputum smear conversion during TB treatment. This study aimed to analyze the difference in Acid-Fast Bacilli (AFB) smear conversion at the 2nd and 5th months between TB patients with DM and those without DM. This study used a descriptive comparative design with secondary data from TB patients recorded in 2023–2024 at the Sepulu Community Health Center Laboratory, Bangkalan, Madura. A total of 117 patients met the inclusion criteria. Data were analyzed using the Chi-square test with SPSS version 25. The results showed a significant difference in AFB smear conversion between TB-DM and TB non-DM patients. At the 2nd month, a significant difference was found (p < 0.001). Similarly, at the 5th month, a significant difference was observed (p = 0.009). TB patients with DM tended to experience slower sputum smear conversion compared with patients without DM. These findings indicate that Diabetes Mellitus may influence the effectiveness of TB treatment, particularly in the sputum conversion phase.